ANALISIS KONTRASTIF ONOMATOPE BAHASA JEPANG DAN BAHASA JAWA - Supangat, Nur; Astuti, Sri; IHANR, Elizabeth (Japanese Literature, 2015)
In writing this essay the author discusses the 'Contrastive Analysis of Onomatopoeia in Japanese and Javanese'. The author chose this title because of the lack of discussion about the comparison between the onomatopoeic Japanese and Javanese. To write this thesis, firstly, the author collected data, and then analyze the data, after that, the dat presented in a descriptive form. Onomatopoeia in Japanese consists of two types, namely giseigo (giongo) andgitaigo incorporated in onshouchougo. Giseigo (giongo) are words that express mock voices or sounds of living beings and inanimate objects, while gitaigo are words that express the state. Classification giseigo (giongo) is divided into two, namely giseigo stating voice imitation of living things, and giongo stating imitation sounds of inanimate objects. Just as giseigo (giongo), gitaigo divided into three classifications. The classifications, namely gitaigo who declared a state of inanimate objects, giyougo who declared a state (state behavior) of living creatures, and gijougo who declared a state of heart (feeling) human. Of all these classifications outline has ten different meanings classification. Moreover, the characteristic forms contained on onomatopoeia also affect its meaning.